2018
DOI: 10.1002/bmc.4394
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dissipation kinetics of thiophanate‐methyl and its metabolite carbendazim in apple leaves using a modified QuEChERS–UPLC–MS/MS method

Abstract: As one of the main fungicides for the apple leaf disease control, thiophanate-methyl (TM) mainly exerts its fungicidal activity in the form of its metabolite carbendazim (MBC), whose dissipation kinetics is very distinct from that of its parent but has been paid little attention. The aim of this work was to investigate the dissipation kinetics of TM and its active metabolite MBC in apple leaves using a modified QuEChERS-UPLC-MS/MS method. The results showed that TM and MBC could be quickly extracted by this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Different geographical areas, different rainfall, temperature and other environmental factors as well as different crop varieties, and different growing conditions can lead to different half-lives. The half-life values recorded in the present study are similar or lower with the earlier studies conducted in apple, strawberry, cucumber, and grapes were half-lives which are approximately 1.26 in strawberry (Dalia et al 2017), 1 or 5.23-6.03 days in apples (Dalia et al 2017;Wang et al 2019), 4.7-6.5 in grapes (Mandal et al 2010), and 12.3-13.4 days in cucumber (Ali Bassam Al-Obaidie and Sumir 2018).…”
Section: Dissipation Pattern and Safety Periodsupporting
confidence: 89%
“…Different geographical areas, different rainfall, temperature and other environmental factors as well as different crop varieties, and different growing conditions can lead to different half-lives. The half-life values recorded in the present study are similar or lower with the earlier studies conducted in apple, strawberry, cucumber, and grapes were half-lives which are approximately 1.26 in strawberry (Dalia et al 2017), 1 or 5.23-6.03 days in apples (Dalia et al 2017;Wang et al 2019), 4.7-6.5 in grapes (Mandal et al 2010), and 12.3-13.4 days in cucumber (Ali Bassam Al-Obaidie and Sumir 2018).…”
Section: Dissipation Pattern and Safety Periodsupporting
confidence: 89%
“…The results indicated that the established method provided a relatively better performance in terms of sensitivity and accuracy compared to previous approaches and was acceptable for use in the determination of thiophanate-methyl and carbendazim in cowpea samples. 16,[23][24][25] Dissipation and residue distribution of thiophanatemethyl and carbendazim in cowpeas in field trials The residual definition of thiophanate-methyl is expressed as carbendazim, 43 and the estimated residue concentration of thiophanate-methyl is the sum of the concentrations of thiophanate-methyl and carbendazim, which is termed the 'total carbendazim'. When the residual level is >LOQ, thiophanatemethyl is converted into carbendazim equivalents, and the conversion factor is 0.55.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the calculated half-lives of thiophanatemethyl at different spraying dosages were 3.6-7.0 days in grapes 16 and 5.26-6.03 days in apple leaves. 25 Terminal residue trials are the data sources for dietary risk assessments and the establishment of maximum residue limits (MRLs) in certain crops. The terminal residue concentrations of thiophanatemethyl and carbendazim in cowpeas are listed in Tables 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations